2020
DOI: 10.1007/s40899-020-00431-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating watershed health in Costa Rican national parks and protected areas

Abstract: Although the biodiversity of Costa Rican national parks, forests, and wetlands has been extensively surveyed, there has not been a watershed assessment that reflects their baseline water quality. Undoubtedly, the influx of 3.1 million visitors annually can lead to deterioration. Additionally, the country's movement toward 100% carbon neutral energy means reliance on capturing water for the production of hydroelectricity. The missing hydrologic data set is of immediate concern, as watershed health predicts tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…The role of PA has been widely regarded in Costa Rica (Leguía et al, 2008; Kappelle, 2016; Jovanelly et al, 2020), but they did not repair specifically in the wetland ecosystems. Our results demonstrated that the main difference in vulnerability between these ecosystems in Costa Rica are the occurrence of affecting human activities around them in the first place and the land ownership of their location the second.…”
Section: Discussionmentioning
confidence: 99%
“…The role of PA has been widely regarded in Costa Rica (Leguía et al, 2008; Kappelle, 2016; Jovanelly et al, 2020), but they did not repair specifically in the wetland ecosystems. Our results demonstrated that the main difference in vulnerability between these ecosystems in Costa Rica are the occurrence of affecting human activities around them in the first place and the land ownership of their location the second.…”
Section: Discussionmentioning
confidence: 99%
“…Surface water runoff from most protected areas may be a source of pollution in streams, marshes, rivers, lakes, and seas, which is a source of worry in many metropolitan areas [30][31][32]. During precipitation events, vegetation (trees and bushes) intercepts some of the precipitation, while the rest reaches the ground (Figure 16 shows the tree species in the study area and the avoided runoff of each).…”
Section: Avoided Runoffmentioning
confidence: 99%
“…Lo anterior queda evidenciado a partir de la aplicación de los índices de calidad, cuyos resultados permiten argumentar que los patrones de contaminación que prevalecen en la zona generan un efecto similar en la calidad del agua superficial; sin embargo, estos pueden manifestarse afectados en cuanto a variabilidad según la época, aspecto que concuerda con la tendencia general y global de un cuerpo de agua superficial, los cuales son considerados altamente heterogéneos, en términos de calidad de agua, al estudiarse en diferentes épocas (Jovanelly et al, 2020;Qadir, Malik y Husain, 2008;Wu et al, 2018). Particularmente, la mayor afectación de la calidad del agua durante la época lluviosa puede asociarse a la mayor escorrentía de contaminantes al cuerpo de agua que puede materializarse, así como a la alteración de los parámetros de calidad a razón del aumento del volumen de agua en el río (Ayandiran et al, 2018;Phiri et al, 2005;Waziri & Akinniyi, 2012).…”
Section: Determinación De Calidad Del Agua Y Aplicación De íNdices De...unclassified